Data narratives: Increasing scholarly value. Issue 1 (2014) - Pouchard, Line; Barton, Amy; Zilinski, Lisa
ABSTRACT: Data narratives or data stories have emerged as a new form of the scholarly communication focused on data. In this paper, we explore the potential value of data narratives and the requirements for data stories to enhance scholarly communication. We examine three types of data stories that form a continuum from the less to the more structured: the DataONE data stories, the Data Curation Profiles, and the Data Descriptors from the journal Scientific Data . We take the position that these data stories will increase the value of scholarly communication if they are linked to the datasets and to the publications that describe results, and have instructional value.